Pemanfaatan dan Pengembangan Media Digital dalam Pembelajaran Bahasa Indonesia Bagi Penutur Asing: Inovasi, Implementasi Dan Tantangan - Vani Indra Pramudianto; Laily Nurlina Iskandar (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Learning Indonesian for Foreign Speakers (BIPA) is an important means to introduce Indonesian language and culture globally. Rapid digital transformation has brought innovation in BIPA teaching methods, especially through the use of digital media. This article discusses the use of digital media in BIPA learning and the challenges faced. The research method uses literature analysis of ten relevant scientific articles, focusing on digital media innovations such as the e-Tandem model, virtual learning spaces (Cave, Campfire, Watering Hole), and social media applications and special applications. The results of the study show that digital media supports interactive and collaborative learning, expands the reach of teaching, and overcomes geographical barriers. However, there are obstacles such as access to technology and digital skills of teachers. For sustainable effectiveness, the development of digital competency training for teachers is essential. Digital media in BIPA has the potential to promote Indonesian in the international arena and strengthen Indonesian cultural diplomacy.